2015
DOI: 10.1002/ar.23255
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of Diabetes Related Alterations in Human Parotid Gland and Comparison with Submandibular Gland

Abstract: Type 2 diabetes mellitus represents one of the principal diseases that afflict the world population and is often associated with malfunction of salivary glands and consequent oral diseases. We recently described significant ultrastructural alterations in the human submandibular gland in diabetic patients without evident oral pathologies. Herein, an analogs morphometrical investigation was focused on the parotid gland in order to evaluate if one of the two glands is more affected by diabetes. Parotid fragments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…These findings strongly suggest differences among the three glands in the apical membrane dynamics in which PIPKα is involved, indicating that the three salivary glands are discrete not only in histology but also in secretory activity, as recently noted (Isola & Lilliu, ; Lilliu et al. ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings strongly suggest differences among the three glands in the apical membrane dynamics in which PIPKα is involved, indicating that the three salivary glands are discrete not only in histology but also in secretory activity, as recently noted (Isola & Lilliu, ; Lilliu et al. ).…”
Section: Discussionsupporting
confidence: 80%
“…are discrete not only in histology but also in secretory activity, as recently noted (Isola & Lilliu, 2015;Lilliu et al 2015). Although this is the first report of PIP5Ka activity confined to the acinar cells in salivary glands, several studies have reported the apical plasmalemmal localization of endogenous PIP5Ka and b in cultured renal collecting tubular cells, another polarized epithelial cell type similar to the glandular acinar cells (Weixel et al 2007;Szalinski et al 2013).…”
Section: Discussionsupporting
confidence: 64%
“…At first sight, these results might be suggestive of increased melatonin secretion, in the event of selective exocytosis of these granules. However, considering the results of our recent morphometric investigation, an alternative interpretation can be proposed (Lilliu et al, , ). We suggest that in the diabetic condition, granule emptying is hampered, probably because the granules cannot fuse with the luminal membrane and hence are unable to discharge their content in the lumen of the gland.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the morphology of the parotid and submandibular glands is differently affected in diabetes. Acinar size and granule area were significantly increased in diabetic submandibular glands compared to non‐diabetic submandibular glands, whereas both parameters remained unaltered in diabetic parotid samples (Lilliu et al, , ). The present findings provide evidence that parotid and submandibular glands differ from each other in their susceptibility to alterations related to diabetes as well as to other pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that, among the major salivary glands, parotid is the most involved in melatonin release. It is noteworthy that the degree of participation to melatonin supply represents a further feature distinguishing the salivary glands from one another, in addition to many anatomical, embryonic, histochemical and metabolic diversities .…”
Section: Discussionmentioning
confidence: 99%